Competitive interactions between two fishing fleets in the North Sea. (16th March 2016) - Sys, Klaas; Poos, Jan Jaap; Van Meensel, Jef; Polet, Hans; Buysse, Jeroen
Abstract: We examine whether the landing rates of Belgian beam trawlers in the Southern Bight of the North Sea were affected through competitive interactions with the Dutch beam trawler fleet and whether the development of a pulse trawler fleet has altered competitive interactions between both fleets. Effects of competition were investigated through a natural experiment based on the different weekly exploitation patterns of both fleets. Logbook data were used to fit a generalized additive mixed model for the daily landing rates of the target species sole ( Solea solea ) and plaice ( Pleuronectes platessa ). Results showed that landing rates of sole by the Belgian beam trawlers (>221 kW) from 2006 to 2013 were lower during weekdays than during weekends when the Dutch trawler fleet is in harbour, while no such an effect was found for plaice. After the development of a pulse trawler fleet in 2011, the negative weekday effect in the sole landing rates was much more pronounced in 2012 and 2013. This increased loss of efficiency during weekdays, as a result of increased competition with the Dutch trawler fleet, coincided with a reallocation of fishing effort by the Belgian beam trawler fleet.